2000
DOI: 10.1038/sj.leu.2401726
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation of HL60 human leukaemic cells to cytotoxic drug-induced apoptosis by inhibition of PI3-kinase survival signals

Abstract: Drug resistance remains a serious limiting factor in the treatment of acute myeloid leukaemia (AML) either at initial presentation or following primary or subsequent relapses. Using specific kinase inhibitors, this study has investigated the contribution of the Ras/PI3-kinase regulated survival pathways to drug resistance and suppression of apoptosis in a cell line derived from AML (HL60). Inhibition of the Raf/MAP-kinase (ERK) pathway with a specific MAP-kinase inhibitor, apigenin did not sensitise HL60 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 64 publications
3
54
0
Order By: Relevance
“…50 A study investigating this possibility demonstrated that inhibition of PI3-kinase survival Leukemia signals, with concomitant inhibition of PKB, in the acute myeloid leukaemia (AML)-derived cell line, HL60, which endogenously expresses an activated N-Ras mutation, greatly increased sensitivity to cytotoxic drug-induced apoptosis. 42 Similar findings were reported by a second group, where PI3-kinase inhibition accelerated daunorubicin-induced apoptosis in the monocytic cell line, U937. 59 Deregulated PKB is evident in a variety of tumours, due to PKB overexpression, constitutive activation by oncogenic Ras, or following inactivation of the tumour suppressor, PTEN.…”
Section: Figuresupporting
confidence: 83%
See 4 more Smart Citations
“…50 A study investigating this possibility demonstrated that inhibition of PI3-kinase survival Leukemia signals, with concomitant inhibition of PKB, in the acute myeloid leukaemia (AML)-derived cell line, HL60, which endogenously expresses an activated N-Ras mutation, greatly increased sensitivity to cytotoxic drug-induced apoptosis. 42 Similar findings were reported by a second group, where PI3-kinase inhibition accelerated daunorubicin-induced apoptosis in the monocytic cell line, U937. 59 Deregulated PKB is evident in a variety of tumours, due to PKB overexpression, constitutive activation by oncogenic Ras, or following inactivation of the tumour suppressor, PTEN.…”
Section: Figuresupporting
confidence: 83%
“…Likewise, no specific inhibitor of either PKB or JNK has been identified to date. A role for PI3-kinase in chemoresistance in vitro has only recently been reported 42,59 and the potential (and toxicity) of the PI3-kinase inhibitors LY294002 and wortmannin have not yet been clinically evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations